2015
DOI: 10.1111/sms.12574
|View full text |Cite
|
Sign up to set email alerts
|

Social background, bullying, and physical inactivity: National study of 11‐ to 15‐year‐olds

Abstract: More children from lower social backgrounds are physically inactive than those from higher ones. We studied whether bullying was a mediating factor between lower social background and physical inactivity. We also examined the combined effect of low social class and exposure to bullying on physical inactivity. The Danish sample of the Health Behaviour in School-aged Children (HBSC) study 2006 included 6269 schoolchildren in three age groups: 11-, 13-, and 15-year-olds from a random sample of 80 schools. The stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
29
4
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(39 citation statements)
references
References 36 publications
4
29
4
2
Order By: Relevance
“…Parents may determine adolescents' exposure to a number of factors that are enablers or barriers to PA, such as motivation to engage in PA and that may explain our findings in line with previous research (Gustafson & Rhodes, 2006;Lawman & Wilson, 2012). Several mechanisms are underpinning parental impact on PI such as direct modelling of PA, establishing or eliminating barriers to PA or sports, and positively reinforcing adolescents for participation in sports (Henriksen et al, 2015). According to our findings, we also posit the socioeconomic-environmental factors as determinants of PI in youth people from families with lower affluence, rather than support the statement that PA is a determinant of health and illness per se, as previously have been posited (Colley et al, 2011).…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…Parents may determine adolescents' exposure to a number of factors that are enablers or barriers to PA, such as motivation to engage in PA and that may explain our findings in line with previous research (Gustafson & Rhodes, 2006;Lawman & Wilson, 2012). Several mechanisms are underpinning parental impact on PI such as direct modelling of PA, establishing or eliminating barriers to PA or sports, and positively reinforcing adolescents for participation in sports (Henriksen et al, 2015). According to our findings, we also posit the socioeconomic-environmental factors as determinants of PI in youth people from families with lower affluence, rather than support the statement that PA is a determinant of health and illness per se, as previously have been posited (Colley et al, 2011).…”
Section: Discussionsupporting
confidence: 83%
“…Both questionnaires measure the same construct, i.e. time spent being moderate-to vigorously active outside school (minutes), which allowed us compare MVPA and VPA and the dimensions of PA between the groups, in line with prior research (World Health Organization, 2010;Muthuri et al, 2014;Chinapaw, Mokkink, van Poppel, van Mechelen & Terwee, 2010;Katzmarzyk et al, 2013;Henriksen et al, 2015). Additionally, the other measures of sedentary behaviours and additional measures of PA consistently confirmed that Colombians were less commonly active compared to Danish, independently of the cut-off used to define being physically active.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…In recent decades, physical inactivity has been identified as an important public health problem globally [1,2]. A number of initiatives aimed at encouraging more physical activity have emerged in an effort to tackle this issue [3][4][5].…”
Section: Introductionmentioning
confidence: 99%
“…There is a combined effect on physical inactivity of the low social class and the bully. However, cyber bullying is not handled separately from bullying as a result of this study [28].…”
Section: Body Image-obesity-eating Habits-eating Attitude Disorders-pmentioning
confidence: 99%